Radiofrequency thermocoagulation of haemorrhoids: learning curve of a novel approach. Issue 3 (17th March 2023) - Butnari, Valentin; Mansuri, Ahmer; Kaul, Sandeep; Shatkar, Veeranna; Boulton, Richard
Abstract: Haemorrhoidal disease (HD) is a common condition that often requires surgical treatment. In comparison with other traditional techniques, radiofrequency thermocoagulation (RFTC) has multiple advantages to traditional repairs and can be a good alternative in surgical management of HD. We retrospectively analysed 20 patients with Grades 2 ( n  = 6, 30%) and 3 ( n  = 12, 70%) haemorrhoids undergoing RFTC from 1 September 2019 to 31 December 2021. Outcomes including post-operative (PO) pain, immediate/late PO complications, recurrence and patient satisfaction were assessed. Twenty cases were included in this case series. All pathological symptoms showed significant improvement in PO period. Eight complications were noted, including minor bleeding ( n  = 2), bleeding that required admissions ( n  = 3), pain ( n  = 2) and recurrence ( n  = 1). The mean time off work is 7 days and all patients were satisfied or very satisfied PO as per telephone questionnaire. RFTC is a safe and effective solution in the management of HD and is a good alternative to conventional procedures.